Answer:
The answer to this question can be described as follows:
-5 with multiplicity 3
9 with multiplicity 2
-1 with multiplicity 1
Explanation:
Given:
![\Rightarrow f (x) = (x + 5)^3(x - 9)^2(x + 1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/i3iebnr7zz66vrbj1mn0o9o093fxvtlmuc.png)
Solve the above equation:
![\Rightarrow f (x) = (x + 5)(x + 5)(x + 5)(x - 9)(x - 9)(x + 1)\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/owuqu3ugukr9ig0rhq5d48joyhg745xteo.png)
The roots of the polynomial are as follows:
![\Rightarrow (x-x_1)(x-x_2)(x-x_3)......(x-x_n)\\\\\Rightarrow x_1,x_2,x_3.........x_n](https://img.qammunity.org/2021/formulas/mathematics/high-school/wz33z5jb39ej1pskojjyro41n2us1id7v1.png)
That's why the roots are:
5 with multiplicity 3
9 with multiplicity 2
-1 with multiplicity 1